Histopathological growth patterns of colorectal liver metastasis exhibit little heterogeneity and can be determined with a high diagnostic accuracy - Höppener, Diederik J.; Nierop, Pieter M. H.; Herpel, Esther; Rahbari, Mohammad; Doukas, Michael; Vermeulen, Peter B.; Grünhagen, Dirk J.; Verhoef, Cornelis Kees (Clinical & experimental metastasis, 2019)
Colorectal liver metastases (CRLM) exhibit distinct histopathological growth patterns (HGPs) that are indicative of prognosis following surgical treatment. This study aims to assess the reliability and replicability of this histological biomarker. Within and between metastasis HGP concordance was analysed in patients who underwent surgery for CRLM. An independent cohort was used for external validation. Within metastasis concordance was assessed in CRLM with ≥ 2 tissue blocks. Similarly, concordance amongst multiple metastases was determined in patients with ≥ 2 resected CRLM. Diagnostic accuracy [expressed in area under the curve (AUC)] was compared by number of blocks and number of metastases scored. Interobserver agreement (Cohen’s k) compared to the gold standard was determined for a pathologist and a PhD candidate without experience in HGP assessment after one and two training sessions. Both the within (95%, n = 825) and the between metastasis (90%, n = 363) HGP concordance was high. These results could be replicated in the external validation cohort with a within and between metastasis concordance of 97% and 94%, respectively. Diagnostic accuracy improved when scoring 2 versus 1 blocks(s) or CRLM (AUC = 95.9 vs. 97.7 [p = 0.039] and AUC = 96.5 vs. 93.3 [p = 0.026], respectively), but not when scoring 3 versus 2 blocks or CRLM (both p > 0.2). After two training sessions the interobserver agreement for both the pathologist and the PhD candidate were excellent (k = 0.953 and k = 0.951, respectively). The histopathological growth patterns of colorectal liver metastasis exhibit little heterogeneity and can be determined with a high diagnostic accuracy, making them a reliable and replicable histological biomarker.